RUANG REKREASI TERBUKA PUBLIK ORGANIK: STUDI 4 LOKASI DI KAWASAN PERKOTAAN YOGYAKARTA - , DWI BAGAS KURNIADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The number of immigrants who settled in Yogyakarta have made the city very heterogeneous. Yogyakarta experienced a shift in culture, so that the community's needs and lifestyle changes including recreation. Types of recreational activities favored by young people is gathered in one place, spend the time to chat and interact with other people or known by the term ' nongkrong '. The increasing number of formal activities in the community caused a recreational public open space to actualize a non formal activities reduced. The limitations of recreational public open space provided by the Government in the end cause society finding and using free space as a container in the implementation of its activities. Currently, the availability of public open space are incompatible with the needs of society. The community eventually formed the public open spaces independently and purely organic in Yogyakartaâs urban area. The interesting phenomenon was subsequently appointed as a research topic with the title of organic recreational public open space in Yogyakartaâs urban area. The purpose of this research is to identify the various characteristics of the organic recreational public open space and the reason the formation of typology as happened today. This study describes the results of the exploration of the phenomenonâs reconstruction that occurs on site research with qualitative approach. Characteristics of public space is formed by three basic components, namely physical settings, activity, and perception of space user. In the settings space, dominating character in Yogyakarta is an open space which has no rigid border. In activity components, its character is dominated by activities not scheduled time. In the perception of users, public spaces function as gathering place spontaneously. Quality of recreational public open space is very dependent from this aspect of the attraction, which supports amenitas attractions, and good accessibility.